Acoustic analysis of prosody in Sydenham's chorea - Oliveira,Patrícia M (2010)
There are few studies of language and speech in patients with Sydenham's chorea (SC). We have done an acoustic analysis of fundamental frequency (F0), duration and intensity of declarative and interrogative sentences made by 20 SC patients, 20 patients with rheumatic fever (RF) without chorea, and compared them with 20 healthy age-matched controls (CO). Each group included 12 females. We found that there is no difference between the RF and CO groups in all studied parameters. Patients with SC, however, presented with a speech characterized by decreased F0 range (difference between minimum and maximum F0), shorter duration of sentences, and higher intensity of the first syllable of sentences. The findings were not influenced by the nature of the sentences (i.e. , declarative or interrogative), but for all variables they were significantly more severe in males than females. In conclusion, we have demonstrated that patients with acute SC have an impairment of modulation of F0 and longer duration of emission of sentences, resulting in a monotone and slow speech. This pattern is similar to what has been described in other basal ganglia illnesses, such as Parkinson's disease, Huntington's disease and Wilson's disease.